Recovery of Beach-Foredune Vegetation after Disturbance by Storms - Gallego-Fernández, Juan B.; Morales-Sánchez, José A.; Martínez, M.Luisa; García-Franco, José G.; Zunzunegui, María (Journal of coastal research, 2020)
Gallego-Fernández, J.B.; Morales-Sánchez, J.A.; Martínez, M.L.; García-Franco, J.G., and Zunzunegui, M., 2020. Recovery of beach-foredune vegetation after disturbance by storms. In: Malvárez, G. and Navas, F. (eds.), Global Coastal Issues of 2020. Journal of Coastal Research, Special Issue No. 95, pp. 34–38. Coconut Creek (Florida), ISSN 0749-0208. Beaches and foredunes are characterized by being exposed to harsh environmental restrictions mainly due to salt spray, burial by sand and occasional storms. In response to this, plant species from these habitats have adaptations that allow them not only to survive in these environments, but also to recover after the impact of disturbances such as severe storms. In this study, we had the opportunity to study vegetation recovery on the coast of Huelva, Spain, after the impact of a strong winter storm in 2017 which severely affected the vegetation growing on the beach and foredune. Species composition and abundance of vegetation was compared before (2013) and after (2018) the storm hit the coast in 2017. The results show that the effects of the storm were still evident a year later. Native species, mainly perennials, were able to recover almost completely to predisturbance levels. In contrast, the invasive species, Oenothera drummondii, which was abundant before the storm, disappeared from the beach and its presence in the foredune was greatly reduced. Given the forecasts of sea level rise and the increased frequency and intensity of storms, it is necessary to sustain and reinforce the natural coastal sectors where native plant communities maintain the resilience of coastal ecosystems when impacted to these disturbances.